Dirāsatun Taḥlīliyyatun Naḥwiyyatun ‘an Musytaraki Lafẓy Fī Sūrati al Rūmi wa Ṭuruqu Ta’līmihā - Pane, Ahmad Ridona (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2022)
In this research it consists of 4 problems: What is the word contained in the common verbal in Surat Al-Roum?, What are the syntax and meanings of the vocabulary contained in the lexicon in dictionaries?, What is the interpretation and meaning of the vocabulary contained in the common word in Surat Al-Roum?, What are The appropriate way to teach the verbal participant? The objectives of the research in this research: to find out the word contained in the verbal consonant in Surat Al-Rum. To know the syntax and meanings of the vocabulary contained in the common verbal in dictionaries. To know the interpretation and meanings of the vocabulary contained in the verbal common in Surat Al-Rum. To know the appropriate method in teaching the verbal participant. As for the research method, the researcher uses the descriptive qualitative research method in this research. The data sources in this research are divided into two parts: the main sources and the secondary sources. The main sources are the Holy Qur'an, especially from Surat Al-Rum and Al-Tafsir. As for the secondary sources in obtaining data from the library or previous research reports and from books of semantic science or books related to the verbal subscriber. As for the method of data collection, the researcher uses the documentary and library method. The method of research analysis by analyzing some general data (Analysis Data General Prtial). The results of the research in this research: that in Surat Al-Rum it is found that the number of verses in Surat Al-Rum is 60 verses, and that Surat Al-Rum falls in the twenty-first part according to the arrangement of the Ottoman Qur’an. And that the number of the verbal common in Surat Al-Roum is 21 common words in the pronunciation, and they are: a few, the hour, kindergarten, dirt, apparent, command, human, affection, supplication, face, partners, sects, party, sultan, the poor, the values, they say, they pave We hit mushrooms, we tasted them